Elasticidade de substituiç\~ao das importaç\~oes no Brasil - Honorio Kume; Guida Piani (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– Estimates of the impacts on imports due to trade agreements depend fundamentally on the elasticity of substitution between imports from different foreign suppliers. This paper estimate the elasticity of substitution for Brazilian imports, for 42 sectors of input-output table for 2005, highlighting the differences in transportation costs and the effectively paid tariffs between products, depending on the country of origin. The elasticities obtained are statistically significant for 1% to 39 sectors, with the arithmetic average of 6.6 and the amplitude of 4.7 and 13.7. The availability of the own elasticities for Brazil will provide more accurate calculations of the effects of a possible Brazilian participation in new trade liberalization agreements.
Keywords: F13; 330; Außenhandelselastizität; Brasilien